2013
DOI: 10.3390/ma6030713
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Luminescence Properties of Lu2O3:Eu3+ F127 Tri-Block Copolymer Modified Thin Films Prepared by Sol-Gel Method

Abstract: Lu2O3:Eu3+ transparent, high density, and optical quality thin films were prepared using the sol-gel dip-coating technique, starting with lutetium and europium nitrates as precursors and followed by hydrolysis in an ethanol-ethylene glycol solution. Acetic acid and acetylacetonate were incorporated in order to adjust pH and as a sol stabilizer. In order to increment the thickness of the films and orient the structure, F127 Pluronic acid was incorporated during the sol formation. Structural, morphological, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…16) 19) These films can be deposited on the substrate by several techniques, including "spin-coating", "spray-coating", "dip-coating", and "electrophoresis". 20)24) The immersion method known as "dipcoating" has many advantages such as the possibility of coating large surfaces, the simplicity of the equipment, and a low cost.…”
Section: )8)mentioning
confidence: 99%
“…16) 19) These films can be deposited on the substrate by several techniques, including "spin-coating", "spray-coating", "dip-coating", and "electrophoresis". 20)24) The immersion method known as "dipcoating" has many advantages such as the possibility of coating large surfaces, the simplicity of the equipment, and a low cost.…”
Section: )8)mentioning
confidence: 99%
“…Bands around ~1430-1100 cm −1 are observed, which In addition, bands associated with the carbonyl groups (-COOH) ~1725-1700 cm −1 are observed and attributed to the stretching bond of the lutetium acetate precursor employed, and are completely removed at 600 • C, which is an indicator of the moment of the beginning of crystallization process [8]. Bands around ~1430-1100 cm −1 are observed, which correspond to the symmetric and asymmetric vibrations of the C-H bonds, probably from the use of Pluronic F-127; however, as can be observed, they disappear at 700 • C [35,36]. Next, at 500 • C, bands related to the crystallization of LuVO 4 can be observed at ~810-830 cm −1 and ~446-455 cm −1 , which correspond to the V-O bonds of the vanadate group (VO 2 3− ) and Lu-O, respectively [2].…”
Section: Chemical Evolution and Structural Propertiesmentioning
confidence: 75%
“…Table 1 shows the (200) preferential orientation-index α200 of the prepared films, and as observed, it practically does not present changes due to the effect of temperature increase, remaining at approximately 0.90, which shows that the orientation process was carried out from low temperatures and, once the material crystallized, the system tends to maintain that orientation. It is worth mentioning that when Pluronic F-127 acid is used, in some studies, it has been shown that it changes the size of the particles and their orientations [36][37][38][39][40][41][42][43], which is a very It is evident that the increment in the annealing temperature increases the crystallization of the films. At 600-650 • C, the broad peak centered at ~25-25.5 • is typical for the amorphous structure obtained by the xerogel formation by the sol-gel process [40].…”
Section: Chemical Evolution and Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of the europium-doped powders reveals a mix of homogeneous spherical particles, well distributed, of approximately 1 and 4 µm in size. The morphological analysis of the Gd 2 O 3 :Eu 3+ films with Gd:S = 1:2 revealed a porous surface with round particles promoted by the high F-127 concentration in the layers 34 . It is well known that the presence of this molecule (F-127) in the sol plays a crucial role in synthesizing surfactant-modified ceramic films.…”
Section: Morphological Characteristicsmentioning
confidence: 96%